Structural evolution of massive galaxies in the last 11 Gyr - Buitrago Alonso, Fernando (2012)
This thesis describes the properties and evolution of massive ($M_{stellar}≥10^{11} h_{70}^{-2} M_{\odot}$) galaxies at $0 < z < 3$, including their relationship to lower mass systems. Present-day massive galaxies are composed mostly of early-type objects, although it is unknown whether this was also the case at higher redshifts. In a hierarchical assembling scenario the morphological content of the massive population is expected to change with time from disk-like objects in the early Universe to spheroid-like galaxies at present. We first probe this theoretical expectation by compiling a large sample of massive galaxies in the redshift interval 0$<$z$<$3. Our sample of 1082 objects is composed of 207 local galaxies selected from the Sloan Digital Sky Survey, plus 875 objects observed with the HST from the POWIR/DEEP2 Survey and the GOODS NICMOS Survey. 639 of our objects have spectroscopic redshifts. Our morphological classification is done in the V-band restframe both quantitatively (using the S\'ersic index as a morphological proxy) and qualitatively (by visual inspection). Using both techniques we find a significant change in the dominant morphological class with cosmic time. The fraction of early-type galaxies among the massive galaxy population has changed from $\sim$20-30% at z$\sim$3 to $\sim$70% at z=0. Spheroid-like galaxies have been the predominant morphological massive class only since z$\sim$1. This morphological evolution is so far based on the detailed morphological analysis of these objects, which ultimately rests on the shape of their surface brightness profiles. To explore the consistency of this scenario, we examine the kinematic status of a small subset of these galaxies. We have observed in the H-band 10 massive galaxies at $z\sim1.4$ with the Integral Field Spectrograph SINFONI at VLT. Our sample of galaxies have been selected purely by their photometric stellar mass without accounting for any morphological criteria a priori, and having [OII] line equivalent widths of $> 15 Å$ to secure their kinematical measurements. Through a 3D kinematical spectroscopy analysis we conclude that half (i.e. 50$±$7%) of our galaxies are compatible with being rotationally supported disks in agreement with our previous photometric expectations. This is around a factor of two higher than what is observed in the present Universe for objects of the same stellar mass. Strikingly, the majority of these massive galaxies show clear and fairly large rotational velocity maps, implying that massive galaxies acquire rapidly rotational support and hence gravitational equilibrium. In addition, we have evidence, based on our measured velocity dispersions and imaging, to favour a picture in which minor (and major) mergers are the main driving force behind the evolution of this massive galaxy population. There is also cumulative evidence showing that the formation process for a number of these massive galaxies occur at even higher redshifts ($z > 5$) and that their morphological features are preserved when observing them in the UV restframe. Hence, we made use of the excellent capabilities of GNS to locate and study massive galaxies beyond $z = 3$ within our imaging and secondly determining whether the strong mass-size relation found for the most massive objects holds as well for lower mass objects. Our findings show the extreme compactness of massive objects at $z > 3$ and only a moderate evolution in size below our $10 {11} M_{\odot}$ mass limit.